2012
DOI: 10.5761/atcs.oa.11.01733
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results after the Box Pulmonary Vein Isolation Procedure for Chronic Atrial Fibrillation in Mitral Valve Surgery

Abstract: Background: We hypothesized that chronic atrial fibrillation (AF) originated from the pulmonary veins, and was maintained by irregular activations of the posterior left atrium. We had performed the box pulmonary vein isolation procedure for the elimination of chronic AF associated with solitary mitral valve disease from 1999 to 2004. This paper evaluated the long-term results of this procedure over more than 6 years, and discussed the role of the pulmonary veins and posterior left atrium in maintaining AF. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Thus, with the focus on the PV triggers, surgeons began performing an increasing number of minimal-access PVI procedures. 197 , 1369 , 1370 , 1371 However, investigators showed that this treatment was inadequate for patients with persistent and long-standing persistent AF. 1355 This led to the belief that the persistent forms of AF needed both substrate modification and trigger isolation , and this provided the impetus to develop the Dallas lesion set, which replicated all the LA lesions of the Cox-Maze III, yet allowed them to be placed on the surface of the full-beating LA.…”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“…Thus, with the focus on the PV triggers, surgeons began performing an increasing number of minimal-access PVI procedures. 197 , 1369 , 1370 , 1371 However, investigators showed that this treatment was inadequate for patients with persistent and long-standing persistent AF. 1355 This led to the belief that the persistent forms of AF needed both substrate modification and trigger isolation , and this provided the impetus to develop the Dallas lesion set, which replicated all the LA lesions of the Cox-Maze III, yet allowed them to be placed on the surface of the full-beating LA.…”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“…14,15 Additional incisions and use of cryolesion were used in these previous studies. 14, 15 Sueda and colleagues 16 reported a series of 53 patients who had the PV isolated in MV surgery with a surgical technique very similar to ours. They reported a freedom from AF recurrence rate of 70.6% at 6 years after the operation.…”
Section: Discussionmentioning
confidence: 67%
“…Restricting the ablation lines to the area of the left atrium which is most affected by structural remodelling, the posterior LA wall, is appealing. Creation of a box including the posterior LA wall and PVs during mitral valve surgery in patients with (longstanding) persistent AF resulted in AF-free survival of 71 % after 6 years follow-up [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral thoracoscopic chest tubes were inserted. Two guidance catheters were introduced through the oblique and transverse sinuses from the left to the right-sided chest tube as previously described [ 9 ]. A bipolar RF clamp (Cardioblate Gemini S, Medtronic Inc., Minneapolis) was attached to the guidance catheters and positioned to encircle the left PVs and posterior left atrium (Fig.…”
Section: Methodsmentioning
confidence: 99%